2006
DOI: 10.1097/01.hjh.0000198023.53859.a2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a home blood pressure monitoring programme on therapeutic compliance in hypertension: the EAPACUM–HTA study

Abstract: An HBPM programme using electronic monitors is effective in improving compliance in arterial hypertension, measured using the MEMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 17 publications
3
96
0
6
Order By: Relevance
“…Some studies have reported that home BP measurements might improve patients' drug compliance and increase physicians' concern about their patients' BP control by improving patients' compliance with hypertensive management and by increasing the availability of information on patients' BP. 28,29 Halme et al 30 found that intermittent self-measurement of BP improved BP control compared to ordinary treatment in a multicenter, randomized, parallel-group study in a primary health-care setting. Therefore, it appears that home BP measurements improve the management of hypertension.…”
mentioning
confidence: 99%
“…Some studies have reported that home BP measurements might improve patients' drug compliance and increase physicians' concern about their patients' BP control by improving patients' compliance with hypertensive management and by increasing the availability of information on patients' BP. 28,29 Halme et al 30 found that intermittent self-measurement of BP improved BP control compared to ordinary treatment in a multicenter, randomized, parallel-group study in a primary health-care setting. Therefore, it appears that home BP measurements improve the management of hypertension.…”
mentioning
confidence: 99%
“…Drug compliance is essential in pharmaceutical care. As previous studies have reported that home BP measurements are associated with good medication compliance 38,39 and the present population measured home BP, patients' compliance might be better in the present population compared with that in other populations.…”
Section: Discussionmentioning
confidence: 43%
“…Of eleven randomized controlled trials, six (54%) reported a significant improvement in compliance attributable to self-measurement of blood pressure. 40 In this way, control of blood pressure was higher, 41 and the patients were more satisfied by this approach, which did not increase the cost of treatment. 42 The success of such an approach is even greater if self-monitoring, Internet support, and pharmacy management are used together.…”
Section: The Therapeutic Environmentmentioning
confidence: 91%